Legal Regulation of Land Protection as one of the Directions for Preventing Corruption - Mozghovyi, Oleksandr; Kolomoitsev, Vitalii; Korniienko, Maksym; Liutikov, Pavlo; Marchenko, Olesia (Jurnal Cita Hukum, 2024)
The study aims to analyse global trends in land use and conservation in the activities of state administrations as one of the directions for preventing corruption. Main content the study analysed global trends in state management in land use and conservation as one of the directions for preventing corruption. The results show that the use of land resource potentials in the world's countries is carried out by considering the environmental safety requirements stipulated in the land region's strategic documents. Considering Ukraine's European integration intentions, a tool for rural area development based on the ecosystem approach is proposed. Methodology The materials and methods of the study are based on the analysis of documentary sources. The basis is a dialectical method of recognising the phenomena of social reality, and based on this dialectical method, mainly formal and comparative legal approaches are used. Conclusion The experience of the EU and countries around the world shows that the priority of national administrations (land administrations) in land use and conservation is the ecosystem approach to the conservation and regeneration of land and other natural resources, which can be achieved through the maintenance of common agricultural policies, the creation of funds to support farmers, the provision of technical assistance, national and targeted programs for development and long-term development planning. The general trend in European Union countries is to develop land sector development strategy documents that look 5-10 years ahead.